2020
DOI: 10.5152/ejbh.2020.5305
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Tumor Infiltrating Lymphocytes in Triple Negative Breast Cancer

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Based on the postoperative pathological results of patients in this study, TILs were correlated with pathological grade, peritumor vascular invasion, molecular typing and other factors, which were in agreement with the conclusions of previous studies (Pruneri et al, 2016b;Criscitiello et al, 2020;Dülgar et al, 2020). In addition, this study innovatively found that BRCA peri-tumor nerve invasion was also negatively correlated with TILs, providing another influencing factor as a reference, although the specific mechanism still needs to be further explored.…”
Section: Validation Of Nomogram In Nat Patientssupporting
confidence: 90%
“…Based on the postoperative pathological results of patients in this study, TILs were correlated with pathological grade, peritumor vascular invasion, molecular typing and other factors, which were in agreement with the conclusions of previous studies (Pruneri et al, 2016b;Criscitiello et al, 2020;Dülgar et al, 2020). In addition, this study innovatively found that BRCA peri-tumor nerve invasion was also negatively correlated with TILs, providing another influencing factor as a reference, although the specific mechanism still needs to be further explored.…”
Section: Validation Of Nomogram In Nat Patientssupporting
confidence: 90%
“…Several studies have shown that histopathological TME components, particularly TILs, can be used to predict pCR because increased counts of sTILs and tTILs have been correlated with pCR in TNBC patients [30,31]. TILs mirror the local immune response, and high TIL counts are associated with favorable OS in patients with TNBC [32][33][34]. Although H&E WSIs can be used to enumerate TILs, they do not provide information on the various types of TILs in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that histopathological TME components, particularly TILs, can be used to predict pCR because increased counts of sTILs and tTILs have been correlated with pCR in TNBC patients (27,28). TILs mirror the local immune response, and high TIL counts are associated with favorable OS in patients with TNBC (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%